Laccase Activity in CTAB-Based Water-in-Oil Microemulsions - Azimi, Maryam (Iran J Pharm Res, 2016)
The aim of this study was to develop a microemulsion system as a medium for laccase-catalyzed reactions. Phase behavior studies were conducted by constructing partial pseudo-ternary phase diagrams for systems comprising of cetyltrimethylammonium bromide (CTAB), various organic solvents as the oil phase (i.e., hexane, cyclohexane, heptane, octane, isooctane, toluene, isopropyl myristate), two co-surfactants (i.e., 1-butanol and 1-hexanol) and citrate buffer solution, at various surfactant/co-surfactant weight ratios (R(sm)). A monophasic, transparent, non-birefringent area (designated as microemulsion domain) was seen to occur in some phase diagrams along the surfactant/organic solvent axis, the extent of which was dependent mainly upon the nature of co-surfactant and R(sm). On each phase diagram, three different water-in-oil (w/o) microemulsion systems with less than 50 wt% surfactant mixture and less than 20 wt% of aqueous phase were selected for laccase loading and activity measurements. Results revealed that the catalytic activity of laccase in CTAB-based w/o microemulsions decreased considerably, compared with its activity in the buffer solution, the extent of which depended upon the type of component and their compositions in the microemulsions. It was suggested that the conformational changes due to the electrostatic interactions between the cationic head group of CTAB and the negative enzyme might be the reason for the reduction of laccase activity, once entrapped in the microemulsion.